Trigeminal neuralgia due to pontine infarction - (:unkn) unknown (WILEY-BLACKWELL, 2004)
Trigeminal neuralgia (TN) is most commonly caused by vascular compression of the trigeminal nerve root entry zone. Secondary trigeminal neuralgia due to ischemic lesion of the pons is very rare. Here we report a patient with a pontine infarct transecting the central trigeminal pathways resulting with trigeminal neuralgia.
Keywords: infarction; ischemia; pons; trigeminal neuralgia; MULTIPLE-SCLEROSIS; LINEAR PONTINE; ROOT LESIONS; PATHOGENESIS